Pengaruh Pemberian Pembiayaan KUR Syariah terhadap Peningkatan Omzet UMKM: Studi Kasus PT. Pegadaian Syariah Sinabang - Taria, Elvi; Husen, Tamitha Intassar (Medan Resource Center, 2022)
This article aims to discuss the Effect of Providing Sharia KUR Financing on Increasing MSME Turnover, Case Study of PT. Sinabang Sharia Pawnshop. It is hoped that this article will be able to provide input to the competent authorities in order to maximize MSME lending given the importance of the business unit's role in the Indonesian economy, especially when the COVID-19 type corona virus outbreak is currently sweeping the world. With the characteristics of SMEs that are more flexible compared to large industries, SMEs are able to revive the vibrancy of the Indonesian economy as happened after the 1997-1998 monetary crisis in Indonesia previously. This research took place at PT. Pegadaian Syariah Sinabang by taking 78 research samples of UKM actors who are taking care of KUR loans. Based on the results of the study, it was found that the provision of KUR had a positive impact on increasing turnover, but the policy of granting KUR still depended on the assets that were pledged as collateral because credit service providers did not dare to take the risk of bad credit.